The contribution of local wisdom in the Nagasasra textbook as support for the Pancasila student profile strengthening project (P5) - Nurhidayati, Nurhidayati; Suwarna, Suwarna; Wulan, Sri Hertanti; Niswah, Nujumun; Zarbaliyeva, Laura (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
The Merdeka Curriculum places strong emphasis on students' character development, which is operationalized through the Pancasila Student Profile Strengthening Project (P5) comprising six core dimensions. As one of the primary curricular resources, textbooks are expected to reflect and mediate these character values in classroom learning. This study aims to examine the contribution of Javanese local wisdom represented in the Nagasasra textbook to supporting the implementation of P5. Employing a qualitative descriptive design, this research adopts a document-based analysis of the Nagasasra Javanese language textbooks for grades X, XI, and XII. Data were collected using a read-and-record technique and analyzed through systematic coding, categorization, and thematic interpretation, following the analytical procedures proposed by Miles, Huberman, and Saldaña, as well as Creswell and Creswell. The units of analysis included words, phrases, sentences, discourse, illustrations, and Javanese idiomatic expressions embedded in the textbook content. The findings indicate that the Nagasasra textbook integrates Javanese local wisdom across all six dimensions of the Pancasila Student Profile, with prominent emphasis on piety, respect for diversity, mutual cooperation, independence, critical thinking, and creativity. The study underscores the potential of culturally grounded textbooks to function as pedagogical instruments for integrating local wisdom into character education and for strengthening the implementation of the Merdeka Curriculum in secondary education.